The Developing of Simple e-Learning based on the Flipped Classroom with VBL and DGBL for Junior High School Student Learning EFL (Tarbiyah Suska Conference Series, 2022)
Living with a pandemic for around three years made our education improve and update with technology. Mastering English as a popular language is a tool to gain more knowledge and experience in this era. This study researched the learning EFL with flipped classrooms based on video-based learning on youtube and digital game-based learning for junior high school students in Riau Island. In this study, the researcher put the content of EFL about time, and the student learns through the explanation in the video before they study in the classroom; in the classroom teacher gives or asks a question or answers the student. The data was obtained by observation and online tests. The data was analysed by measuring of N-Gain score calculation. The result is not every junior high school student in Indonesia can apply to learn with e-learning for flipped classrooms. And the flipped classroom with VBL and DGBL is more effective than the traditional method.
Keywords: e-learning, EFL, Video-Based Learning, Flipped Classroom, DGBL.